2016
DOI: 10.1007/s00424-015-1785-2
|View full text |Cite
|
Sign up to set email alerts
|

Adult nephron-specific MR-deficient mice develop a severe renal PHA-1 phenotype

Abstract: Aldosterone is the main mineralocorticoid hormone controlling sodium balance, fluid homeostasis and blood pressure by regulating sodium reabsorption in the Aldosterone Sensitive Distal Nephron (ASDN). Germline loss-of-function mutations of the mineralocorticoid receptor (MR) in humans and in mice lead to the "renal" form of type 1 pseudohypoaldosteronism (PHA-1), a case of aldosterone resistance characterized by salt wasting, dehydration, failure to thrive, hyperkalemia and metabolic acidosis. To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
6
34
0
Order By: Relevance
“…Interestingly, we also observed that the two days of dietary sodium restriction lowered plasma K + levels in mice. Consistent with a dominant role of plasma K + , two groups were just able to show that the down-regulation of NCC in mice with kidney-specific MR deletion could be overcome or at least mitigated by employing dietary K + restriction to normalize plasma K + [6,28]. Likewise, recent studies using mice deficient for 11βHSD2 by Hunter and colleagues challenged the conventional concept of mineralocorticoid signaling in the DCT [10].…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, we also observed that the two days of dietary sodium restriction lowered plasma K + levels in mice. Consistent with a dominant role of plasma K + , two groups were just able to show that the down-regulation of NCC in mice with kidney-specific MR deletion could be overcome or at least mitigated by employing dietary K + restriction to normalize plasma K + [6,28]. Likewise, recent studies using mice deficient for 11βHSD2 by Hunter and colleagues challenged the conventional concept of mineralocorticoid signaling in the DCT [10].…”
Section: Discussionmentioning
confidence: 93%
“…Inducible kidney tubule‐specific MR KO (tubular MR KO) mice display a severe pseudohypoaldosteronism type 1 phenotype characterized by weight loss, increased urinary Na + excretion, hyponatremia, hyperkalemia, and high plasma aldosterone levels . This phenotype is attributed to decreased Na + reabsorption and K + secretion along the ASDN.…”
Section: Resultsmentioning
confidence: 99%
“…The previously described doxycycline‐inducible kidney tubule‐specific and mosaic MR‐deficient mice were used for experiments. Kidney tubule‐specific MR knockout (KO) induced by administration of doxycycline hydrochloride (2 mg/mL in drinking water) for 15 days to 4‐week‐old mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When challenged with a low sodium diet, however, the mice had increased sodium and water excretion and loss of body weight. Two more recent independent studies have deleted the MR along the mouse adult nephron via a tamoxifeninducible Pax 8-Cre recombinase transgene from four weeks (Canonica et al 2016) and eight weeks (Terker et al 2016) of age. In contrast to the MR AQP2Cre mutant mice, adult MR Pax 8-Cre mice in both studies showed features of severe PHA-1 on a normal sodium diet, significant weight loss, high urinary sodium excretion, hyperkalaemia and elevated plasma aldosterone.…”
Section: Epithelial Cell-specific Deletion Of the Mr Genementioning
confidence: 99%